2019
DOI: 10.1016/j.celrep.2019.04.080
|View full text |Cite
|
Sign up to set email alerts
|

ACC Theta Improves Hippocampal Contextual Processing during Remote Recall

Abstract: Highlights d ACC leads CA1 during remote recall d ACC theta modulates CA1 spiking and gamma power during remote recall d ACC and CA1 ensemble context information increases over consolidation d Consolidation increases the strength and spread of ACC theta effects on CA1 networks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 131 publications
3
11
0
Order By: Relevance
“…In the current experiments, our control group had decreased ACC–hippocampus coherence during error trials, indicating a lack of communication between these areas and replicating the purest essence of neural synchrony hypothesis (i.e., synchrony supports information transfer enabling cognitive success). Similar theta range effects have been found in spatial working memory and long-term memory tasks before in rodents 53 , 54 , 95 , macaques 96 , and in humans 97 , 98 . Thus, it is quite remarkable that we found that in STZ animals coherence between the ACC and hippocampus was decreased on correct trials.…”
Section: Discussionsupporting
confidence: 78%
“…In the current experiments, our control group had decreased ACC–hippocampus coherence during error trials, indicating a lack of communication between these areas and replicating the purest essence of neural synchrony hypothesis (i.e., synchrony supports information transfer enabling cognitive success). Similar theta range effects have been found in spatial working memory and long-term memory tasks before in rodents 53 , 54 , 95 , macaques 96 , and in humans 97 , 98 . Thus, it is quite remarkable that we found that in STZ animals coherence between the ACC and hippocampus was decreased on correct trials.…”
Section: Discussionsupporting
confidence: 78%
“…This notion is supported by our findings that ACC-CA1 cross-regional interaction, but not region-autonomous ACC activity, is enhanced during the remote session (Figures 2D, 3C, 3D, and S1B). Consistent with this, a recent study has found that non-aversive contextual re-exposure at the remote time point enhances ACC-CA1 crossregional interaction (Wirt and Hyman, 2019), suggesting that the recruitment of ACC-CA1 pathway at remote recall may be a general mechanism common to multiple forms of memory. Furthermore, although we cannot exclude the possibility that non-freezing periods engage cognitive processes in addition to recall, such as updating, extinction, and reconsolidation, we did observe a strong correlation between ACC-entrained CA1 synchronous firing during these periods and freezing levels (Figures 4D and 4E), suggesting an active role in recall.…”
Section: Discussionsupporting
confidence: 61%
“…Additional evidence for the neocortex-to-hippocampus information flow was found in oscillatory and spiking activity patterns during the retrieval of old, consolidated memory. When rodents are re-exposed to a neutral (Wirt & Hyman, 2019) or aversive context (Makino, Polygalov, Bolaños, Benucci, & McHugh, 2019) 1 month later, theta oscillations in the ACC become strongly synchronized with those in the hippocampus. The analysis of the directionality of oscillatory coupling revealed that ACC theta oscillations lead hippocampal theta oscillations.…”
Section: The Hippocampus Instructs the Maturation Of Neocortical Memory Traces Through The Coordinated Reactivation Of Memory Traces In Tmentioning
confidence: 99%